Oxford Word Skills. Elementary Vocabulary. Learn to use the most important words and phrases in English topic by topic - Gairns R. Ruth (Oxford, Oxford University Press, 2022)
The first level in a three-level topic-based vocabulary course to learn and practise the words that learners need to know at each CEFR level, based on the Oxford 3000TM. Oxford Word Skills improves students' vocabulary and vocabulary-learning skills. Short, clear presentations and lots of opportunity for practice give students the confidence to use new vocabulary. 100 units at each level mean they cover a huge range of topics and everyday situations. The Oxford Advanced Learner’s Dictionary app, or OALD app, provides pronunciation and more information about the meaning and usage of words. learn over 2,400 words and phrasesimprove your vocabulary-learning skillspractise the words in contextstudy 100 units (20 extra with more practiceuse in the classroom and/or for self-studyThe first level in a three-level topic-based vocabulary course to learn and practise the words that learners need to know at each CEFR level, based on the Oxford 3000TM. Oxford Word Skills improves students' vocabulary and vocabulary-learning skills. Short, clear presentations and lots of opportunity for practice give students the confidence to use new vocabulary. 100 units at each level mean they cover a huge range of topics and everyday situations. The Oxford Advanced Learner’s Dictionary app, or OALD app, provides pronunciation and more information about the meaning and usage of words. learn over 2,400 words and phrasesimprove your vocabulary-learning skillspractise the words in contextstudy 100 units (20 extra with more practiceuse in the classroom and/or for self-study.